Kombinasi Pendekatan Diminish dan Rebuild dalam Manajemen Krisis di Sektor Transportasi Laut - Fadeliyah Ikhwan; Muh. Akbar; Muliadi Mau; Rikha Pratiwi (Publikasi Indonesia, 2026)
The maritime transportation sector is highly susceptible to situational crises, such as vessel accidents, which can rapidly damage organizational reputation and erode public trust; effective crisis communication is therefore essential to reputation restoration. This research aims to explore the effectiveness of a combined